2016
DOI: 10.1002/kin.21053
|View full text |Cite
|
Sign up to set email alerts
|

Complex Nonlinear Behavior in the Bromate–2‐Aminophenol Reaction

Abstract: The bromate–2‐aminophenol reaction in a batch reactor was investigated in this research, in which both simple and sequential oscillations were observed. The occurrence of sequential oscillations were found to be very sensitive to changes of the initial concentrations, where decreasing the concentration of sulfuric acid or sodium bromate or increasing the 2‐aminophenol concentration caused the two oscillation windows to coalesce. Lowering the reaction temperature from 30 to 5°C also caused the two oscillation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…We attempted to identify the origin of the occurrence of the “trumpet”‐shape and sequential oscillations in the BZ‐system containing oxalacetic acid by assuming that during the reaction decomposition of oxalacetic acid to pyruvic acid is taking place. This assumption seemed to be reasonable considering that (i) OAA can indeed decompose to pyruvic acid by decarboxylation and (ii) the reason for the sequential oscillation has been also assumed in systems in which besides the starting substrate, additional substrate (co‐substrate) that was formed from the latter during the reaction was also present as suggested for the 2‐aminophenol‐bromate oscillating system . In order to check whether pyruvic acid that might have been formed from OAA is present in parallel with OAA, pyruvic acid in the absence of OAA was added to the BZ‐system in similar concentrations to those were applied in the OAA‐containing BZ‐system, however, in these cases no oscillations have been found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attempted to identify the origin of the occurrence of the “trumpet”‐shape and sequential oscillations in the BZ‐system containing oxalacetic acid by assuming that during the reaction decomposition of oxalacetic acid to pyruvic acid is taking place. This assumption seemed to be reasonable considering that (i) OAA can indeed decompose to pyruvic acid by decarboxylation and (ii) the reason for the sequential oscillation has been also assumed in systems in which besides the starting substrate, additional substrate (co‐substrate) that was formed from the latter during the reaction was also present as suggested for the 2‐aminophenol‐bromate oscillating system . In order to check whether pyruvic acid that might have been formed from OAA is present in parallel with OAA, pyruvic acid in the absence of OAA was added to the BZ‐system in similar concentrations to those were applied in the OAA‐containing BZ‐system, however, in these cases no oscillations have been found.…”
Section: Resultsmentioning
confidence: 99%
“…Of the known chemical oscillators, the Belousov‐Zhabotinsky (BZ) reaction has been one of the most extensively studied oscillatory reactions so far, which involves the oxidation of an organic substrate such as citric acid or malonic acid by acidic bromate in the presence of catalyst including metal or complex ions such as cerium(III)‐ion or ferroin, respectively ,. Furthermore, it has been shown that the ferroin‐catalyzed BZ‐system can even exhibit complex oscillation behaviors, i. e., sequential oscillations at various reactant concentrations . Moreover, many of these BZ‐systems require mixed substrates such as malonic acid (MA) and e. g. 1,4‐cyclohexanedione (1,4‐CHD) to reveal complex oscillation behavior such as sequential oscillations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UBO substrates are oxidizable organic compounds, such as derivatives of phenol or AN or their precursors, e.g., cyclohexane-1,4-dione. , The BZ system in both standard and modified versions has served for decades as an experimental and theoretical model in the study of nonlinear phenomena such as chemical oscillations, chaos, and traveling waves . In particular, the UBOs and catalyzed BZ reactions with aromatic substrates remain the focus of current research in the field of nonlinear dynamics as their mechanisms are still generally not known. Such research could open new insights into the oxidation pathways of organic substrates, help to clarify the role of free radicals in such reactions, and explore interactions between the organic and inorganic counterparts of oscillators from both the chemical and nonlinear dynamics points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, bromate-based reaction systems are the most extensively investigated and best understood chemical oscillators, which involve the oxidation and bromination of an organic substrate by acidic bromate. In the past two decades, a host of aromatic compounds have been found to be capable of reacting with acidic bromate to exhibit spontaneous oscillations even in the absence of metal catalysts and have seen increasing use due to the lack of the formation of gas molecules, which is a desired property when the system is employed to explore pattern formation in reaction–diffusion media. , The reaction of phenol with acidic bromate, for example, has been found to give rich nonlinear behavior, , and derivatives of phenol such as 4-aminophenol have also been found to result in oscillatory behavior when reacting in acidic bromate solution, although some cases require the presence of external illumination. The continuous supply of organic substrate through desulfonation of PSA makes the proposed chemical system similar to a semiopen bromate–aromatic compounds oscillator. , Such a dynamic property provides opportunities of significantly prolonging the oscillatory window and discovering new phenomena.…”
Section: Introductionmentioning
confidence: 99%